2017
DOI: 10.4155/tde-2016-0080
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Efficacy of Ultrasound, Sonosensitizers and Chemotherapy: A Review

Abstract: Chemotherapeutic agents, either in the form of systemically injected free drug or encapsulated in nanoparticles transport vehicles, must overcome three main obstacles prior to reaching and interacting with their intended target inside tumor cells. Drugs must leave the circulation, overcome the tissue-tumor barrier and penetrate the cell's plasma membrane. Since, many agents enter the cell by endocytosis, they must avoid entrapment and degradation by the intracellular endolysosome complex. Ultrasound has demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 67 publications
1
35
0
Order By: Relevance
“…These data support the hypothesis that the possible mechanism of action for effective sonodynamic anticancer response derives from the ROS elicited by the US activation of the sensitiser, such as in the well-clinically established PDT technique where cancer cell killing is achieved through oxidative stress. We thus feel, as do other authors [60][61][62], that sonodynamic treatment deserves further investigation for its potential as an intriguing strategy for cancer treatment.…”
Section: Discussionsupporting
confidence: 51%
“…These data support the hypothesis that the possible mechanism of action for effective sonodynamic anticancer response derives from the ROS elicited by the US activation of the sensitiser, such as in the well-clinically established PDT technique where cancer cell killing is achieved through oxidative stress. We thus feel, as do other authors [60][61][62], that sonodynamic treatment deserves further investigation for its potential as an intriguing strategy for cancer treatment.…”
Section: Discussionsupporting
confidence: 51%
“…VLIUS has been utilized for cancer therapy studies - sonodynamic therapy, US mediated chemotherapy, US mediated gene delivery and antivascular US therapy [34]. Focused US has been used recently to target DNA-loaded microbubbles located within tumor’s neovasculature to facilitate release of genetic material locally into the tumor [35, 36]. In particular, US has been noted causing the process of sonoporation thus producing transient pores in the cancer cell membranes through which molecules are able to enter the cell [20, 37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to increase the efficacy of HIFU. Many studies have confirmed that both microbubbles and SDT can improve the efficacy of HIFU [15, 16, 35]. The N 2 O-loaded microbubbles prepared in this study have a smaller particle size, but similar characteristics as ultrasonic microbubble contrast agents.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, microbubbles as an exogenous cavitation nucleus also reduce the tissue cavitation threshold and enhance the cavitation effect of HIFU as it passes through the blood circulation into the tumor tissue [14]. In recent years, studies have indicated that sonodynamic therapy (SDT) can synergistically enhance HIFU treatment efficacy [15, 16]. The interactions between the sonosensitizers and ultrasound produce reactive oxygen species (ROS), including singlet oxygen and hydroxyl radicals, which kill tumor cells and inhibit tumor growth via apoptosis and necrosis [17].…”
Section: Introductionmentioning
confidence: 99%